Acute head-fixed recordings in awake mice with multiple Neuropixels probes - Durand, Séverine; Heller, Greggory R.; Ramirez, Tamina K.; Luviano, Jennifer A.; Williford, Allison; Sullivan, David T.; Cahoon, Alex J.; Farrell, Colin; Groblewski, Peter A.; Bennett, Corbett; Siegle, Joshua H.; Olsen, Shawn R. (Nature protocols, 2023)
Multi-electrode arrays such as Neuropixels probes enable electrophysiological recordings from large populations of single neurons with high temporal resolution. By using such probes, the activity from functionally interacting, yet distinct, brain regions can be measured simultaneously by inserting multiple probes into the same subject. However, the use of multiple probes in small animals such as mice requires the removal of a sizable fraction of the skull, while also minimizing tissue damage and keeping the brain stable during the recordings. Here, we describe a step-by-step process designed to facilitate reliable recordings from up to six Neuropixels probes simultaneously in awake, head-fixed mice. The procedure involves four stages: the implantation of a headframe and a removable glass coverslip, the precise positioning of the Neuropixels probes at targeted points on the brain surface, the placement of a perforated plastic imaging window and the insertion of the probes into the brain of an awake mouse. The approach provides access to multiple brain regions and has been successfully applied across hundreds of mice. The procedure has been optimized for dense recordings from the mouse visual system, but it can be adapted for alternative recording configurations to target multiple probes in other brain areas. The protocol is suitable for users with experience in stereotaxic surgery in mice. Simultaneous electrophysiological recordings are obtained from multiple brain regions using Neuropixels probes. The procedure covers the implantation of a headframe, the targeted positioning of probes and their insertion through a perforated imaging window.